Design and Realization of Memory-Based Chirp Generator on Synthetic Aperture Radar (SAR) - Bagas Dwi Putera; Erfansyah Ali; Heroe Wijanto; M. Ramdhani (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2018)
Synthetic Aperture Radar (SAR) is a radar system that uses platform movement combined with signal processing. Eventhough it use a small antenna, SAR produce high resolution as good as a large antenna. In SAR imaging, radar is mounted on a moving platform. It transmits electromagnetic pulses and receives backscattered echo signals. Transmitted pulses are subsequently scattered by earth surface and only small portion of them are received by antenna. SAR transmitted signals normally is a chirp or linear frequency modulation (LFM) signal. Chirp signal can be generated by using the analog and digital generator. Digital chirp generator is divided into two methods which are the memory-based and direct digital synthesizer (DDS). The difference of these two methods is located in the memory ROM. In this study, we designed and realized digital chirp generator by using Field Programmable Gate Array (FPGA) DE-1 development board for SAR implementation. It operates in 1.27 GHz (L Band) frequency and had a bandwith of 10 MHz with 24 MHz sampling rate. We found that the output of FPGA is well performed for chirp signal in digital domain.